Information requirements analysis for holonic manufacturing systems in a virtual environment - Manesh, Hamed Farahani; Schaefer, Dirk; Hashemipour, Majid (Springer London Ltd, 2011)
The design and development of holonic manufacturing systems requires careful, and sometimes risky, decision making to ensure that they will successfully satisfy the demands of an ever-changing market. In this paper, the authors propose a methodology for a holonic manufacturing systems requirement analysis that is based on a virtual reality approach and aimed at assisting designers of such systems along the entire systems design and development process. Exploiting virtual reality helps the user collect valid information quickly and in a correct form by putting the user and the information support elements in direct relation with the operation of the system in a more realistic environment. A prototype software system tool is designed to realise the features outlined in each phase of the methodology. A virtual manufacturing environment for matching the physical and the information model domains is utilised to delineate the information system requirements of holonic manufacturing systems implementation. A set of rules and a knowledge base is appended to the virtual environment to remove any inconsistency that could arise between the material and the information flows during the requirement analysis.
Keywords: Information requirements analysis; Holonic manufacturing systems; Virtual reality; Virtual factory